Transverse analysis of full-scale precast segmental box girder segments with corrugated steel webs: Experimental tests and FE modelling. (15th May 2019) - Zhou, Man; Liu, Yunyi; Deng, Wenqin; Hassanein, Mostafa Fahmi; Zhang, Hong
Highlights: A full-scale model test of the precast segmental box girder with CSWs is carried out. The bending failure of the top flange precedes shear buckling failure of the CSWs. Two methods for enhancing the transverse stiffness of the CSWs are proposed. Abstract: The world's first full-scale model test of the precast segmental box girder with corrugated steel webs (CSWs) is carried out in this study to examine the applicability of using the precast segmental construction technology in erecting the composite girder bridges with CSWs. This study focuses on the transverse mechanical performance of bridge segments under vehicle loads; based on the fact the transverse bending stiffness of segmental box girders with CSWs is weaker than that of bridge girders with concrete webs. It is found from the experimental results that that bending failure of the top concrete flange occurs first instead of the shear buckling of the CSWs. In addition, the result of load testing indicate that the precast segmental box girder with CSWs has a high coefficient of safety margin and a good plastic deformability. This study also presents two improved schemes of structural design to enhance the structural transverse stiffness and reduce the accumulated deformation differences caused by the self-weight in the process of segmental precasting by the short-line method.